Molecular basis for H blood group deficiency in Bombay (Oh) and para-Bombay individuals. - Kelly, R J (1994)
The penultimate step in the biosynthesis of the human ABO blood group oligosaccharide antigens is catalyzed by alpha-(1,2)-fucosyltransferase(s) (GDP-L-fucose: beta-D-galactoside 2-alpha-L-fucosyltransferase, EC 2.4.1.69), whose expression is determined by the H and Secretor (SE) blood group loci (also known as FUT1 and FUT2, respectively). These enzymes construct Fuc alpha 1-->2Gal beta-linkages, known as H determinants, which are essential precursors to the A and B antigens. Erythrocytes from individuals with the rare Bombay and para-Bombay blood group phenotypes are deficient in H determinants, and thus A and B determinants, as a consequence of apparent homozygosity for null alleles at the H locus. We report a molecular analysis of a human alpha-(1,2)-fucosyltransferase gene, thought to correspond to the H blood group locus, in a Bombay pedigree and a para-Bombay pedigree. We find inactivating point mutations in the coding regions of both alleles of this gene in each H-deficient individual. These results define the molecular basis for H blood group antigen deficiency in Bombay and para-Bombay phenotypes, provide compelling evidence that this gene represents the human H blood group locus, and strongly support a hypothesis that the H and SE loci represent distinct alpha-(1,2)-fucosyltransferase genes. Candidate sequences for the human SE locus are identified by low-stringency Southern blot hybridization analyses, using a probe derived from the H alpha-(1,2)-fucosyltransferase gene.